Botulinum toxin for writer's cramp: a randomised, placebo‐controlled trial and 1‐year follow‐up - Kruisdijk, J J M (BMJ Group, 2007)
BACKGROUND: Botulinum toxin type A (BoNT‐A) has become the treatment of choice for most types of focal dystonia. OBJECTIVE: To investigate the efficacy of BoNT‐A injections in patients with writer's cramp in a double‐blind, randomised, placebo‐controlled trial and to evaluate the follow‐up results. METHODS: Forty participants were randomised to treatment with either BoNT‐A or placebo injections in two sessions. Trial duration was 12 weeks. The primary outcome measure was the patients' choice to continue with the treatment, despite its possible disadvantages. Secondary outcome measures included several clinical rating scales on the levels of impairment and disability. Assessments were made at baseline and 2 months (secondary outcomes) and 3 months (primary outcome). Duration of follow‐up was 1 year. RESULTS: 39 patients completed the trial. Fourteen of 20 patients (70%) receiving BoNT‐A reported a beneficial effect and chose to continue treatment, versus 6 of 19 patients (31.6%) in the placebo group (p = 0.03). The changes on most of the clinical rating scales were significantly in favour of BoNT‐A. Side effects reported were hand weakness, which was mostly mild and always transient, and pain at the injection site. After 1 year, 20 of 39 patients were still under treatment with a positive effect. CONCLUSION: Treatment with BoNT‐A injections led to a significantly greater improvement compared with placebo, according to patients' opinion and clinical assessment scales. Weakness in the hand is an important side effect of BoNT‐A injections, but despite this disadvantage, most patients preferred to continue treatment. About 50% of our patients were still under treatment after 1 year.